Few-Shot Cross-Lingual NER Robustness to Domain Shifts in Low-Resource Languages - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 15 peer-reviewed papers addressing the following research question: How robust are few-shot cross-lingual NER performance gains from large autoregressive models to domain shifts, as evaluated on the WikiANN benchmark in low-resource languages. 14 claims were extracted from source literature; 3 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 4.8/10. This report is a machine-generated
Machine-generated literature synthesis.